Lung mechanics and hyperpolarised gas MRI - Thorpe, James (2018)
Lung diseases affect the lives of millions of people across the UK and result in the thousands of deaths every year. It is therefore vitally important to continue to develop a wide range of diagnostic techniques to improve our understanding of lung diseases and how they can be treated. This thesis provides an overview of the main methods of assessing lung condition before focussing on developments in two specific areas: Forced Oscillation Technique (FOT) and Hyperpolarised (HP) gas MRI. FOT is an inexpensive, non-invasive lung function test that measures the acoustic impedance of the airways by applying an oscillating waveform via a mouthpiece. FOT cannot be used to image the lung but instead provides information on a variety of other physiological parameters. Two FOT studies are presented in this thesis: a multi-site phantom study and a patient based study. The phantom study confirmed the validity of the Nottingham FOT system used in the patient study and investigated the effects of lung stiffness and airway obstruction on measured FOT parameters using a 3D printed lung phantom, as well as comparing phantom results between three different FOT devices (an in-house device from the University of Nottingham, an Erich Jaeger Master-Screen IOS and a tremoFlo C-100 airwave oscillometry system) at two sites (the University of Nottingham and Glenfield Hospital, Leicester). It was found that changes in lung stiffness and airway obstruction are observable in the reactive and resistive (respectively) components of measured impedance. A difference was seen between the Jaeger IOS system and the other two devices. The patient based study was undertaken to investigate the efficacy of FOT, in comparison to spirometry, in differentiating between three patient groups, healthy, asthmatic and chronic obstructive pulmonary disease (COPD), with a particular focus on investigating the effect of a bronchodilator on measured FOT parameters. It was found that both FOT and Spirometry were effective at differentiating between the patient groups, however, they provided different information about patient response to bronchodilator thus demonstrating that both techniques should be performed to obtain the maximum information about a patient’s disease state. HP gas MRI uses isotopes of noble gases, such as 3He and 129Xe, to either image the lungs or perform non-imaging measurements of parameters such as the Apparent Diffusion Coeffcient (ADC). A short study using 3He was performed comparing ADC measurements at two different time scales between two sites (the University of Nottingham, 13ms, and the University of Sheffield, 2ms) with a secondary aim of investigating the effect of age on ADC. A study on HP 129Xe MRI is presented covering developments that have been made in various imaging techniques including breathing protocols and scanning techniques. The objective of this study is to establish a reliable scanning protocol using healthy volunteers before expanding the study to investigate different disease states including COPD and idiopathic pulmonary Fibrosis (IPF). Although progress has been made in testing the validity of various imaging techniques, with ventilation images at 25mm and 10mm slice thicknesses obtained, more development is still needed to improve the quality of the images in order for them to be useful in a clinical setting.